Possible effects of new regulation implementation on pole vault event - Theodorou, A.; Skordili, S. E.; Paradisis, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
According to the Athletics European Team Championships new regulations, which are to be introduced in June 2009, each pole vault event competitor shall be entitled to a maximum of 4 fouls only throughout the whole event. The purpose of the present study was to examine the possible effects that the implementation of the new regulations, would have had on the conduction of the event for males and females. Methods: Male and female pole vault finals official results in Olympic Games, IAAF Outdoor World Athletics Championships and European Outdoor Athletics from 2000 onwards, were analysed. Results: Male pole vaulters (N=102), start the competition at a mean height of 551.29cm (SD±7.96) and conclude at 568.31cm (SD±15.57), with a mean height difference of 17.02cm (SD±12.49). During the event they perform a mean of 6.85 attempts (SD±2.16), classified as either successful (M=2.41, SD±1.15) or failed (M=4.44, SD±1.38). Following the fourth foul 40.20% of them perform failed attempts (M =1.80, SD ±0.98 attempts) and 10.78% successful ones (M=1.36 SD ±0.67 attempts). If the new regulations were applied, athletes would achieve a mean height difference of 15.83cm (SD±4.82) between start and finish. Female pole vaulters (N=93), start the competition at a mean height of 424.19cm (SD±16.46) and conclude at 450.56cm (SD±19.71), with a mean height difference of 26.37cm (SD±13.35). During the event they perform a meane of 8.01 attempts (SD±2.48), classified as either successful (M=3.47, SD±1.59) or failed (M=4.52, SD±1.48). Following the fourth foul 50.54% of them perform failed attempts (M=1.68, SD±1.23) and 12.90% successful ones (M=1.50, SD±0.67 attempts). If the new regulations were applied, female athletes would achieve a mean height difference of 24.91cm (SD±4.82) between start and finish. Discussion: Data demonstrate that the new rules would have resulted in a decrease in the event final performance (6.99% and 5.53% for males and females respectively), due to a mean attempt restrain of 11.13±4.76 and 12.13±6.64, in each final, for males and females respectively. No data however was available for variables such as the time duration of the event and our statistical analyses were based exclusively on the results recorded with the current regulations. Therefore, further research is required before drawing permanent conclusions regarding possible effects on the pole vault event duration and athletes` tactics.